2014
DOI: 10.1007/s00436-014-3783-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, laboratory and pathological findings in cats experimentally infected with Aelurostrongylus abstrusus

Abstract: Aelurostrongylus abstrusus parasitizes the respiratory tract and can heavily affect the breathing and general condition of cats. Experimental infections of six cats were initiated by intragastric administration with 100 or 800 third-stage larvae (L3) obtained from the terrestrial snail Helix aspersa. First-stage larvae were isolated from faecal samples after 35-41 days post infection (dpi) in five animals and until end of study (84 dpi) in two cats. Cough and respiratory sounds were observed starting from 28 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(105 citation statements)
references
References 26 publications
7
91
1
6
Order By: Relevance
“…Infected cats mostly show respiratory signs (Grandi et al 2005;Traversa et al 2008), but nonpathognomic signs (Genchi et al 2014;Schnyder et al 2014) or asymptomatic cats are also commonly observed (Genchi et al 2014). In some cases, an infection with A. abstrusus may result in death (Gerdin et al 2011;Dirven et al 2012;Philbey et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Infected cats mostly show respiratory signs (Grandi et al 2005;Traversa et al 2008), but nonpathognomic signs (Genchi et al 2014;Schnyder et al 2014) or asymptomatic cats are also commonly observed (Genchi et al 2014). In some cases, an infection with A. abstrusus may result in death (Gerdin et al 2011;Dirven et al 2012;Philbey et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As these guidelines do not include specific information on A. abstrusus, the study design was based on scientific knowledge and experience gained in a preliminary study (Schnyder et al 2014). The study designs are summarised in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In general, these guidelines consider a minimum of 6 animals in the control group with at least 5 worms each to be adequate. However, as the guidelines do not include specific recommendations for studies with A. abstrusus and lower infection rates were observed in a preliminary study (Schnyder et al 2014), an infection with at least one worm in each of 6 control animals was deemed to be adequate. Additionally, the lower limit of the 95 % confidence interval was required to be greater than 10 % of the geometric mean.…”
Section: Efficacy Determination and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The infection is usually asymptomatic. However, in the case of an intensive infection of the respiratory system, symptoms such as a chronic cough, dyspnea, nasal discharge, accelerated breathing, loss of appetite and sometimes diarrhoea and anorexia may be observed (4,18,23). The laboratory diagnosis during the prepatent period also presents difficulties due to the lack of diagnostic tests.…”
mentioning
confidence: 99%